PERAN KEPALA MADRASAH DALAM MENERAPKAN KOMUNIKASI UNTUK MENJALIN KERJA SAMA DI MTS AL-WASHLIYAH TEMBUNG - Hasibuan, Leni Hermita; Siahaan, Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Communication is something that cannot be separated from human life as a social creature that is active in integrating every day, including in the world of education, communication has a huge influence and impact, one of which is on the school of Mts Al-Washliyah Tembung. In communicating, it is necessary to have the ability of the head of the madrasah as a leader to convey messages to other people or the community in the school institution, good communication will produce a quality and quality message for the recipient of the message, in which case the message will be able and easily understood after the information that will be conveyed with the purpose of what the message is conveyed. This study discusses how the Role of Madrasah Heads in Communication to Establish Cooperation at Mts Al-Washliyah Tembung which aims to get significant conclusions and information about the extent of the madrasah head's communication ability in carrying out his role as a leader. This study uses Qualitative Research Methods, namely by conducting observations, interviews, and collecting data in the form of documentation directly to the Mts Al-Washliyah Tembung school. Based on the results of observations and interviews, it was immediately found that the Communication of the Head of Madrasah which was initially suspected to be poor in the communication established by a head Madrasah This is quite good. However, it is a little less optimal due to other busyness that results in the head Madrasah often activities outside the Madrasah so that they rarely communicate directly with their subordinates. However, the Madrasah Mts Al-WashliyahTembung continues to communicate indirectly with the direction conveyed to the deputy head of the madrasah to carry out daily meetings and carry out routine recitation once a week.